The Impact Of Employee Voices On Leadership Perspectives - Grace Yulianti (LPPM STIE Kasih Bangsa, 2024)
This research explores the phenomenon of heedful challenging in organizational contexts, focusing on the role of organizational culture and leadershipstudy. The term